Ion beam monitoring over a biased target - Lopes, J. Gabriel (2017)
A specially designed beam profile monitor (BPM) was produced to be assembled over a biased target plate, with the aim of studying the effect of an ion beam deceleration system on the beam fluence due to beam dispersion. The new BPM was developed with a shape as flat as possible, so it could be attached to a biased target plate without affecting the target geometry, using a slit scan method to produce an high-resolution beam profile. This system was designed and installed on the high current ion implanter at the Laboratorio de Aceleradores e Tecnologias de Radiacao, at the Campus Tecnologico e Nuclear, of Instituto Superior Tecnico, in Lisbon. The system is capable of showing the ion beam profile for low-energy ion beams below 15 keV, using a beam deceleration system.